ASGHAR ALI ENGINEER DAN PEMIKIRANNYA MENGENAI TEOLOGI PERDAMAIAN - Idan Dandi (Jurnal Tamaddun : Jurnal Sejarah dan Kebudayaan Islam, 2017)
Asghar Ali Engineer is a progressive Muslim from India. When he was young and young he spent to read and master the works of the great Muslim thinkers of the Syī'ah Ismā'iliyyahal-Musta'āliyyah al-Ṭayyibah who gave him the religious foundation. Moving into adulthood he also did not elude and blind from the fruit of the works of great Western philosophers, such as Bertrand Russell and Karl Marx. The religious and secular education that Asghar Ali Engineer got was not wasted. He applied the sciences in his social life. From these conditions, Ali Engineer developed into an active thinker and daring aspiring both in writing and down the street. Not a few views are devoted in the field of humanitarian, social, political and economic. All of the fields that they do have a purpose that is directed the peace that is wrapped with theology. In this paper, will be discussed the figure of Asghar Ali Engineer and the theology of peace that he brought.Keywords: Peace, Peace Theology, Asghar Ali Engineer